2021
DOI: 10.3390/ma14154284
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Structural Differences on the Mechanical Properties of 3D Integrated Woven Spacer Sandwich Composites

Abstract: Three-dimensional integrated woven spacer sandwich composites have been widely used as industrial textiles for many applications due to their superior physical and mechanical properties. In this research, 3D integrated woven spacer sandwich composites of five different specifications were produced, and the mechanical properties and performance were investigated under different load conditions. XR-CT (X-ray computed tomography) images were employed to visualize the microstructural details and analyze the fractu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…For this study, composite sample materials used were the same as in previous publications, more details about sample materials can be found in the given reference [ 35 ]. Composite materials were supplied by Sinoma Science & Technology Co., Ltd. (Nanjing, China).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this study, composite sample materials used were the same as in previous publications, more details about sample materials can be found in the given reference [ 35 ]. Composite materials were supplied by Sinoma Science & Technology Co., Ltd. (Nanjing, China).…”
Section: Methodsmentioning
confidence: 99%
“…The hand-lay-up process produced five different specifications of 3D integrated woven spacer sandwich composite boards. Three-dimensional integrated woven spacer reinforcement fabrics and sandwich composite samples specifications are given in Table 1 [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…The ability of impact resistance was improved significantly than that of composite without thickened face sheets, and the strength of thickened face sheets dominated the failure. In addition, Zhu et al [ 29 ] found that the core pile height also is a vital parameter for the performance of 3D integrated woven spacer sandwich composites. The force and stiffness decreased with the increase in core pile heights, but the energy absorption capacity increased with increasing core pile heights.…”
Section: Introductionmentioning
confidence: 99%
“…[45][46][47][48][49] The effects of structural parameters of spacer yarn fabric on the mechanical properties of resultant composites were studied in detail. [50][51][52] Electrically conductive carbon fiber in 3D fabric could construct a network and endow composite with EMI shielding properties. Moreover, Fabry-Pérot cavity resonances may occurred in this type of sandwich-like structure, giving a frequencyselective EMI capacity.…”
Section: Introductionmentioning
confidence: 99%